Transformasi Digital: Impak Faktor Kejayaan Kritikal (FKK) Industri 4.0 Terhadap Prestasi Syarikat Pembuatan - Ahmad @ Mohamad, Md Fauzi (Research in Management of Technology and Business, 2022)
Industry 4.0 is a very drastic change that is very influential in our daily life compared to the previous revolutionary era which became a major technology such as cyber physical system, cloud computing, Internet of things (IoT) and manufacturing smart. However, there are several issues related to the performance of manufacturing companies such as low productivity, low value of labor wages, production of product quality that does not meet standards and so on. The purpose of this research is to study the level of Industry 4.0 Critical Success Factors (CSF) in manufacturing companies, study the differences of Industry 4.0 CTR in terms of experience and expectations, and study the impact of Industry 4.0 CSF on performance in manufacturing companies. This study uses FKK as a measure for manufacturing organizations in the application of Industry 4.0 which uses quantitative methods that is to distribute questionnaires and use random sampling techniques using survey questionnaires. This research has used quantitative methods and random sampling techniques by using a survey questionnaire that was answered by a total of 104 respondents from manufacturing companies. The findings show that all FKKs are influential in impact Industry 4.0 in the organizational performance of manufacturing companies. The benefit of this study is to know the FKK Industry 4.0 which plays an important role in influencing the performance of manufacturing companies.